Effects of organic amendment application on soil quality and garlic yield in central-western Argentina - Filippini, Maria Flavia; Abril, Adriana; Cony, Mariano Anibal; Noe, Laura; Venier, Matias; Cónsoli, Daniela; Vallone, Rosana Celia (Bentham Open, 2019)
We analyzed during two garlic crop cycles, the effects of chicken manure and vermicompost on soil chemical and biological properties in an agricultural farm irrigated with municipal wastewater of central-western Argentina. Also we evaluate garlic yield and possible health risks as resulting from the organic amendments and the wastewater use. We found that: a) different doses and types of amendments did not have any significant effects on soil fertility; b) chicken manure and soil before planting, had E. coli and Salmonella spp.; and c) crop yields were quite similar in all treatments, only treatments with 8 Mg ha-1 of both amendments (chicken manure and vermicompost) without N fertilized, were significantly higher than control in both garlic assays. These results are probably the consequence of heavily tilled soils and poor quality of irrigation water with high abundance of enteric bacteria and labile organic matter content. We conclude that to obtain beneficial effects on soil fertility from organic amendment application, wastewater treatment systems must be improved and tillage practices must be reduced.